Schizandrin attenuates lung lesions induced by Avian pathogenic Escherichia coli in chickens. (May 2020) - Yuan, Meng; Peng, Lu-Yuan; Wei, Qian; Li, Jing-He; Song, Ke; Chen, Shuang; Huang, Jiang-Ni; Yu, Jia-Lin; An, Qiang; Yi, Peng-Fei; Shen, Hai-Qing; Fu, Ben-Dong
Abstract: Avian pathogenic Escherichia coli (APEC) can cause serious pathological changes and inflammation in chickens. Schizandrin has anti-inflammatory activity and can prevent damage to various tissues and organs. The purpose of this study was to investigate the protective effect of schizandrin on APEC-induced lung lesions in chickens and explore the potential mechanism of schizandrin protection. The schizandrin (50, 100, and 200 mg/kg) was intragastrically administered for 3 days. APEC was administered using intraperitoneal (i.p.) injection to induce lung lesions. Then, chickens were sacrificed by CO2 inhalation 24 h later and the lung tissues were collected for examining histopathological changes, wet/dry (W/D) ratio, myeloperoxidase (MPO) activity, malondialdehyde (MDA), levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and IL-8 and activation of nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways. Our findings showed that schizandrin markedly inhibited pathological changes, pulmonary edema, MPO activity and MDA content. Moreover, schizandrin markedly reduced the levels of TNF-α, IL-1β, IL-6 and IL-8 in lung tissue. Importantly, the mechanism responsible for these effects was attributed to the inhibitory effect of schizandrin on NF-κB and MAPK signaling activation. In conclusion, our findings reveal that schizandrin displays anti-oxidant and anti-inflammatory activity against APEC-induced lung lesions in chickens, paving the way for rational use of schizandrin as a protective agent against lung-related inflammatory disease. Highlights: The protective effect of schizandrin on APEC-induced lung lesions in chickens was studied. Schizandrin reduced the pathological changes and pulmonary edema of lung tissue induced by APEC-O78. Schizandrin markedly inhibited MPO activity and MDA content in lung tissue. Schizandrin markedly decreased the production of IL-1β, TNF-α, IL-6, and IL-8 in lung tissue. The protective effect of schizandrin on APEC-induced lung lesions was related to NF-κB pathways and MAPK pathways.